2009
DOI: 10.1890/09-0009.1
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and economic analysis of poaching of the greater one‐horned rhinoceros (Rhinoceros unicornis) in Nepal

Abstract: Nepal's greater one-horned rhinoceros (Rhinoceros unicornis) faces serious threats from poaching. Poaching of these rhinos is a complex problem, influenced by such diverse factors as the price of rhino horn on the international market, local socioeconomic factors, and the population dynamics of the species. Few studies have attempted to address this complexity. In this study, we model the poaching and population dynamics of the one-horned rhinoceros within an integrated framework of ecological, socioeconomic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Rhinoceros unicornis is one of the largest living megaherbivores in the world and is now a critically endangered species (Poudyal et al, 2009). One of the unique behaviors of rhinoceroses, including Rhinoceros unicornis is to consistently use the same location for their daily excretion and multiple individuals may deposit dung at this site or midden over several years.…”
Section: Introductionmentioning
confidence: 99%
“…Rhinoceros unicornis is one of the largest living megaherbivores in the world and is now a critically endangered species (Poudyal et al, 2009). One of the unique behaviors of rhinoceroses, including Rhinoceros unicornis is to consistently use the same location for their daily excretion and multiple individuals may deposit dung at this site or midden over several years.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, while GSA techniques do exist, they are presented primarily in mathematical modeling journals (e.g., Saltelli et al 1999) and are not commonly used in research with an applied conservation or resource management focus (but see, e.g., Ellner andFieberg 2003, Pereira et al 2004). For example, in addressing the issue of poaching, which threatens the one-horned rhinoceros in Nepal, Poudyal et al (2009) did not employ a GSA, stating that ''given the large number of variables in our models, a full, factorial sensitivity analysis would be impractical and difficult to interpret.'' Similarly, in a review of 87 spatial population viability models published from 2000 to 2006, Naujokaitis-Lewis et al (2009) found that although sensitivity analyses were conducted in 97% of the studies, none used GSA and only one assessed interactions among input parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of assessing the magnitude of illegal trade and its impacts on local populations of commercially and ecologically valuable species (13,14), it is cryptic and therefore notoriously difficult to quantify (15). Few approaches provide robust delineation of mortality drivers, such as natural mortality versus illegal offtake rates, although this information is critical for diagnosing population trends and risks and formulating regulatory frameworks (16,17 (18).…”
mentioning
confidence: 99%